Perancangan Sistem Informasi Desa Tomuan Holbung Menggunakan Metode Waterfall - Supiyandi Supiyandi; Muhammad Zen; Chairul Rizal; Muhammad Eka (STMIK Budi Darma, 2022)
The settlement of Tomuan Holbung is located in North Sumatra. As a developing town, there is still knowledge that few others have access to through public communication, specifically the internet. As a result, the creation of an information system is required. Human existence is being transformed by technology, which allows us quick and easy access to data. In both government and private institutions, technology helps to organize management systems and work processes. The usage of the Village Information System is one of the IT applications in village life (SID). According to SID's first findings, there are impediments to an existing service, including the absence of functionality of specific features, system loading, and system correctness. The design of a village information system in Tomuan Holbung Village is discussed in this paper. Village information is one of the functions provided by this system. Because of the ready-to-use sample letters that are available. The waterfall process, which includes analysis, design, coding, and testing, as well as entity connection diagrams in database design, was used to create a web-based exam information system. It will be easier for devices to process village information data using a website-based village information system, making it more effective and efficient in giving information about village administration in Tomuan Holbung Village. The information system has a web-based display so that users can alter the material in the system, such as a web-based information system as a means of information in the waterfall method of development in Tomuan Holbung Village